2014
DOI: 10.1016/j.apergo.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring physical exposures and identifying high-risk work tasks within the floor layer trade

Abstract: Introduction-Floor layers have high rates of musculoskeletal disorders yet few studies have examined their work exposures. This study used observational methods to describe physical exposures within floor laying tasks.Methods-We analyzed 45 videos from 32 floor layers using Multimedia-Video Task Analysis software to determine the time in task, forces, postures, and repetitive hand movements for installation of four common flooring materials. We used the WISHA checklists to define exposure thresholds.Results-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Construction work involves heavy activities that can place stress, not only on the low back, but also the peripheral skeleton. Tasks can be highly repetitive and conducted in awkward postures [Mitropoulos et al, 2013; McGaha et al, ]. Work often involves the interface of humans and tools—both powered and not—that can add weight, force, and vibration [Dale et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Construction work involves heavy activities that can place stress, not only on the low back, but also the peripheral skeleton. Tasks can be highly repetitive and conducted in awkward postures [Mitropoulos et al, 2013; McGaha et al, ]. Work often involves the interface of humans and tools—both powered and not—that can add weight, force, and vibration [Dale et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…This sample may not have captured all interventions that were utilized by workers at the time of data collection. As in our previous study (McGaha et al, 2014), we reviewed all videos for clarity to ensure all included videos could be appropriately coded and we used large samples of randomly selected video frames for coding postures and load (Bao et al, 2006). Random frame sampling and computing average exposure times for awkward postures and loads may have caused some exposure misclassification; however, our case series still showed high residual risk to sheet metal workers particularly during prep and installation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Task samples coded as null or not working were excluded from exposures for posture and load. Postures and load were coded within each activity from randomly sampled frames, using methods similar to those described in our previous study of postures and loads among construction floorlayers (McGaha et al, 2014). “Null” codes were assigned for frames with blurry images or obstructed views, and for frames with body angles not aligned with the axis of joint rotation (Lau et al, 2011; Paul et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past literature highlights the occupational physical risks of work tasks among FL and supports a causative relationship between work activities and health claims of the knee 36–40. A few recent studies on FL have found high work-related physical exposures for other body parts including the low back, neck and upper extremities35 41 42 in addition to the knee. The all-fours position (kneeling with the hands on the floor) is commonly used in laying floors since most of the work is performed at the floor level.…”
Section: Discussionmentioning
confidence: 99%